NF-κB1 p50 stabilizes HIF-1α protein through suppression of ATG7-dependent autophagy - Junlan Zhu; Shirui Huang; Yang Li; Jiheng Xu; Ruifan Chen; Mengxin Guo; Xiaohui Qian; Tengda Li; Zhongxian Tian; Honglei Jin; Chuanshu Huang (Cell Death and Disease)
Abstract The function and underlying mechanisms of p50 in the regulation of protein expression is much less studied because of its lacking of transactivation domain. In this study, we discovered a novel function of p50 in its stabilization of hypoxia-inducible factor 1α (HIF-1α) protein under the condition of cells exposed to arsenic exposure. In p50-deficient (p50−/−) cells, the HIF-1α protein expression was impaired upon arsenic exposure, and such defect could be rescued by reconstitutional expression of p50. Mechanistic study revealed that the inhibition of autophagy-related gene 7 (ATG7)-dependent autophagy was in charge of p50-mediated HIF-1α protein stabilization following arsenic exposure. Moreover, p50 deletion promoted nucleolin (NCL) protein translation to enhance ATG7 mRNA transcription via directly binding transcription factor Sp1 mRNA and increase its stability. We further discovered that p50-mediated miR-494 upregulation gave rise to the inhibition of p50-mediated NCL translation by interacting with its 3’-UTR. These novel findings provide a great insight into the understanding of biomedical significance of p50 protein in arsenite-associated disease development and therapy.